Development and local knowledge : new approaches to issues in natural resources management, conservation and agriculture - Bicker, Alan; Sillitoe, Paul, 1949-; Pottier, Johan (Studies in environmental anthropology, 2004)
This book illustrates the growing need for real understanding of local knowledge strategy and its power to assist in positive change.